2018
DOI: 10.1016/j.radi.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in mammography education and training today: The perspectives of radiography teachers/mentors and students in five European countries

Abstract: The short study period allocated to this discipline and lack of material resources were considered the main limitations in mammography education, both impacting on the development of students' skills. Breast positioning, patient communication and quality control were considered key factors affecting mammography performance, patient experience and diagnostic outcome and should therefore be the core focus in mammography education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We strongly believe that E-learning is a good option for continuing education, and this course has been well seek by Portuguese radiographers, since that numerus clausus were fulfilled for both editions. According to Strøm et al [9] the level of emphasis on the acquisition of mammography knowledge, skills and competences of the undergraduate courses in Radiography curriculum differs from one country to another and for both the theoretical component and practical training. For this reason, continuing education and training programmes are demanded by international entities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We strongly believe that E-learning is a good option for continuing education, and this course has been well seek by Portuguese radiographers, since that numerus clausus were fulfilled for both editions. According to Strøm et al [9] the level of emphasis on the acquisition of mammography knowledge, skills and competences of the undergraduate courses in Radiography curriculum differs from one country to another and for both the theoretical component and practical training. For this reason, continuing education and training programmes are demanded by international entities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, radiology curricula and training programmes differs from one educational institution to another. A study conducted by Strøm et al [9] showed that in five European countries (Portugal included) the short period allocated to mammography, for both the theoretical component and practical training, in degree's curriculum and the lack of material resources were the main limitations in mammography education impacting on the development of students' skills. In response to these educational limitations, E-learning approach can play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…For example, students are unable to apply theoretical knowledge in practice and some institutions lack a breast phantom for mammography. Furthermore, recent surveys of students' needs have shown that there is a high demand for practical training to develop positioning skills and learn breast compression techniques 17,18 . Moreover, Radiologic Technology students at two universities in Nigeria have suggested that students' academic performance can be increased if they receive more practical training, with appropriate learning supports and materials.…”
Section: Effectiveness Of In-house Breast Phantom In Mammographic Pos...mentioning
confidence: 99%
“…Strøm et al [10] have studied which are the current challenges in mammography education from the perspectives of radiography teachers, mentors and students. Amongst the main limitations in mammography education were the insufficient study period allocated to this discipline as well as a lack of material resources.…”
Section: Introductionmentioning
confidence: 99%